Technopreneur Design of Marine Aquaculture Based on Multi-Trophic Aquaculture and Tfd-Bakar Batu for Millennials in the Era of Digital Society in Tablolong Kupang Ntt - Daniel Wadu; Aplonia Bani; Deselina Kaleka; Boimau Pither; A Pakro (International Journal Labs, 2023)
Integrated multi-trophic aquaculture (IMTA) is an innovation from conventional cultivation methods or focusing on one species to integrated cultivation of several species together. This study aims to design an entrepreneurial model for technology-based millennials by combining Integrated Multi-trophic Aquaculture (IMTA) and downstream